2019
DOI: 10.1007/s11657-019-0604-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific 1-year mortality rates after hip fracture based on the populations in mainland China between the years 2000 and 2018: a systematic analysis

Abstract: Summary We used statistical approaches to calculate 1-year mortality rates and reveal the relationship between age and the 1-year mortality rate after hip fracture based on data from mainland China between the years 2000 and 2018. Introduction Data on the 1-year mortality rates after hip fracture in mainland China remain limited and localized. We aimed to analyze the 1-year mortality rates and reveal the variations in 1-year mortality by age after hip fracture based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 46 publications
5
33
1
Order By: Relevance
“…The higher mortality in extracapsular hip fractures has been inconsistently reported. 18 This is similar to our results, where the type of fracture did not reach statistical significance in the multivariate exponential regression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The higher mortality in extracapsular hip fractures has been inconsistently reported. 18 This is similar to our results, where the type of fracture did not reach statistical significance in the multivariate exponential regression.…”
Section: Discussionsupporting
confidence: 92%
“…Other factors that are related to 1-year mortality after a hip fracture are serum albuminaemia, socioeconomic status, and the type of fracture. [17][18][19] Given the constant high risk of mortality after one year found in this study, these factors may also affect the long-term outcome.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For patients with hip fractures, the estimated 1-and 2-year morality rates in South Korea were reported to be 16% and 28%, respectively, and the prevalence of osteoporotic fractures as well as the associated societal costs are estimated to increase markedly given that the aging index is expected to increase up to 213.8% by 2030 [36]. In mainland China, the pooled estimate for the 1-year mortality rate following hip fracture was 13.96% between the years 2000 and 2018 [37]. Also, vertebral fractures occurred with a high prevalence in the very elderly population, with an estimated incidence of 30.4% according to the vertebral fracture assessment [38].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high morbidity and mortality, hip fracture has become a major public health issue worldwide. A recent meta-analysis showed that the one year mortality rate was 13.96% after hip fracture in mainland China [ 1 ], and hip fracture was associated with excess short- and long-term all-cause mortality in Europe and USA [ 2 ]. At the same time, hip fracture incidence data suggested that hip fracture rates may be increasing in Poland [ 3 ], France [ 4 ], Japan [ 5 ], Italy [ 6 ], and China [ 7 ].…”
Section: Introductionmentioning
confidence: 99%